The Lonesome Sailing Ship - Reflections on the Rock-Carvings of Sweden and Their Interpreters - Hauptman Wahlgren, Katherine (Current Swedish Archaeology, 2000)
The study of rock-carvings has developed into a separate field of archaeology, often outside the general discourse. The number of works on the subject does not reflect the wide range of interpretations that could be expected. Rather than inspire, the pictorial world has restrained the interpretative discussion. During the first half of the 20th century the religious approach dominated, while the perspective of the 1970s and ’80s focused mainly on mani festations of status. The 1990s marked a revival of interest in the ritual dimension of the rock-carvings. In this article it is argued that rock-carving interpretations ought to be integrated into the wider discourse, as well as into a local context of contemporaneous ancient remains. Another important task for future research is to study the meaning of the carving act, not only the significance of the images.